PEMANFAATAN KIJING LOKAL (Pilsbryoconcha exilis) SEBAGAI BIOFILTRASI LOGAM ARSEN (As) - Muhammad Fikri Darmawan; S.Y. Srie Rahayu; Cecep Sudrajat (EKOLOGIA, 2020)
Heavy metals in waters are a threat to living things both biota that are in these waters, as well as on plants and humans that depend on these water sources. Water quality improvement can be done by utilizing local gravestone (Pilsbryoconcha exilis) as a natural filter. In this study consisted of four treatments and three replications. The amount of gravestone weights of 200 grams, 300 grams and 400 grams acts as a treatment that will later be seen its effect on water containing arsenic metal. The results of this study indicate that local gravestone can reduce arsenic levels in waters with a treatment weight of 400 grams showed the best results with the final result arsenic level of 0.0101 ppm and the highest daily growth rate is 200 grams of weight treatment with a market value of 4.40%.